Maternal stress experiences with neonatal intensive care unit admissions - Tazeem Fatima Ansari; Poonam Wade; Vinaya Singh; Sushma Malik (SpringerOpen, 2022)
Abstract Background Mother experiences variety of stressors related to premature birth, baby's medical condition, unpleasant neonatal intensive care unit (NICU) environment and intuit liability of the infant. Identifying factors that causes stress may be useful in assisting health personnel in understanding their importance and in improving the quality of care. Objective of the study is to assess the stress levels of mothers whose neonate is admitted to the NICU as measured by Parental Stress Scale: Neonatal Intensive Care Unit (PSS: NICU). Methods This prospective analytical study was conducted in NICU of a tertiary care hospital over a period of 12 months after obtaining permission from the institutional ethics committee. The self-administered questionnaire comprising questions on: sights and sounds experienced in NICU, baby's looks and behaviour, parental role and relationship with her baby were collected. The mean score and standard deviation were calculated for each component of PSS: NICU Scale and mean scores are compared. Results Mothers having full term babies have experienced more stress than those having pre-term babies. As measured by PSS-NICU scale the highest mean scores of 2.3 ± 0.57, 4.36 ± 0.53, 4.43 ± 0.58 were obtained for questions "The other sick babies in the room" component of Sight and Sound, "Seeing my baby looking sick" Component of Looks and Behaviour, "Being separated from my baby" Component of Parental Role and Relationship respectively. Conclusion Present study summarises the overall impact of NICU environmental stressors affecting mothers in a developing country and also emphasises the need for further studies in this area for identification of factors that contribute to maternal stress. It may enable health professionals to facilitate mothers' adaptation, thereby promoting optimal mother-infant relationships and subsequent infant development.